The The Influence Of Service Quality, Brand Image, And E-Wom On Consumer Satisfaction - Larasati, Septiana Dewi; Saputro, Edy Purwo (Jurnal Ilmu Manajemen Advantage, 2023)
The primary objective of the research is to determine the extent to which aspects such as the quality of service, the image of the business, and electronic word of mouth influence the overall enjoyment of consumers. For the purpose of this study, a non-probability-based purposive sampling approach was used. The researchers are engaging in deliberate sampling when they design study settings in accordance with the criteria that they have already specified. The majority of the sample will consist of customers who have used the service in the past as well as those who are now using it. This information for the research was gathered via the use of online questionnaires that were distributed. In the course of this research, online questionnaires were used to collect responses from one hundred clients of J&T Express Indonesia. For the purpose of determining whether or not the claims made by the questionnaire were accurate and trustworthy, the researchers examined both the internal and external models by using the Partial Least Square (PLS) methodology and the SmartPLS 3.0 software. Despite the fact that this research did not discover any connection between a good brand image and the level of pleasure experienced by customers, it did discover that electronic word of mouth had a beneficial influence on customer satisfaction. Last but not least, the quality of the service did have an effect on the level of satisfaction experienced by the consumer.